Nomenclature survey of the genus Amaranthus (Amaranthaceae). 5. Moquin-Tandon’s names - Iamonico, Duilio (Phytotaxa, 2016)
A comprehensive nomenclatural study of the 109 names in Acnida, Amaranthus[1] and Euxolus, which were firstly published by Moquin-Tandon, is here presented. 49 names are invalid since 1) were proposed as synonyms under legitimate names (36 names, Art. 36.1c of the ICN), 2) are nomina nuda (11 names, Art. 38.2 Ex. 1 of the ICN), or 3) were uncorrectly named or published (2 names). 10 names are actually new proposed combinations. The remaining 50 names are valid (48 legitimate and 2 illegitimate). Six names (Ac. tuberculata, Am. hybridus var. erythrostachys, Am. sect. Pyxidium, Am. muricatus, E. caudatus var. gracilis, and E. caudatus var. maximus) are already lectotypified, while the remaining ones appears to be untypified. Types (lecto-, isolecto- and neo-) are designated on specimens preserved at BR, G, GH, HAL, HOH, K, MO, MPU, P, UPS, and iconographies by Vellozo (for Am. brasiliensis), Wight (Am. tristis var. wightii), Morandi (Euxolus viridis var. purpurascens), and Dodoëns (Euxolus viridis var. rubens). Syntypes are preserved at BR, MO, RO, and TUB. For the nomenclatural purposes the name Am. lanceolatus was also investigated and lectotypified on a specimen preserved at P. No typifications were proposed for 4 names: Am. paniculatus var. monstruosus (which is to be considered a teratogenous form) Am. flavus var. bernhardi, Am. hypochondriacus var. racemosus, and Am. tristis var. flexuosus. Concerning the latter three names, since the difficult in understanding the concepts of these taxa and finding useful specimens and in the interest of nomenclatural stability, a rejection of is hoped for (Art. 56 of the ICN). New synonymies are proposed for Amaranthus blitum var. nanus (= Am. blitoides), Am. brasiliensis (= Am. cruentus), Am. tristis var. leptostachys (= Am. cruentus), Euxolus viridis var. rubens and Euxolus viridis var. purpurascens (= Am. blitum var. blitum). The name Amaranthus ×wallichii was proposed to formalize a putative hybrid between Am. cruentus and Am. hybridus, which still does not appear to be published.